Integration of the physiological factors determining endurance performance ability - Coyle, E. F. (Exercise and Sport Sciences Reviews, 1995)
This model is used to understand the interrelationships of the physiological factors determining endurance performance ability during prolonged exercise. Early studies found that marathon runners maintain a velocity in competition that corresponds to the intensity at which lactate begins to accumulate in blood and muscle [7, 8, 19]. From this observation, the concept developed that this blood lactate threshold (LT Vo2) reflects the degree of muscular stress, glycogenolysis and fatigue. However, it was not clear whether the lactate accumulation was a result of cardiovascular limitations linked to oxygen delivery, as reflected by Vo2max [54], as opposed to metabolic factors in the exercising muscle related to the extent to which mitochondrial respiration is disturbed to maintain a given rate of O2 consumption [29, 30]. Two studies were performed to determine whether LT Vo2 was tightly coupled to Vo2max. In one study, endurance-trained ischemic heart disease patients were observed to possess a Vo2max that was 18% below that of normal master athletes who followed the patient's training program and who displayed the same performance ability as the patients. Both the patients and the normal men displayed an identical LT Vo2 (i.e., 37 ml/kg/min) (Fig. 2.5). Therefore, performance was determined primarily by LT Vo2 instead of Vo2max in this situation, albeit with abnormal subjects. In a second study we assembled two groups of competitive cyclists who were identical in Vo2max but differed by having a high or low LT Vo2 (82% vs. 66% Vo2max) [13]. When cycling at 80-88% Vo2max, the low LT group displayed more than a 2-fold higher rate of muscle glycogen use and blood lactate concentration, and as a result were able to exercise only one-half as long as the high LT group. Performance time for a given Vo2 was clearly related to LT Vo2 instead of Vo2max (Fig. 2.6). This is not to say that Vo2max plays no role in determining LT Vo2, because as in heart disease patients, it clearly sets the upper limit. Indeed, we have seen that much of the variance (i.e., 31-72%) in LT Vo2 is related to Vo2max. (Fig. 2.11.) However, improvements in performance after the first 2-3 yr of intense training are associated with improvements in LT Vo2, whereas Vo2max generally increases very little thereafter (Table 2.3). The next question concerns the factors responsible for further increases in LT Vo2 and Performance. Another major factor determining LT Vo2 is the muscle's Aerobic Enzyme Activity or mitochondrial respiratory capacity, as discussed in previous reviews [29, 30].